Career Interests Mapping on Economics Education Students in Universitas Muhammadiyah Palangkaraya - Purtina, Arna; Marhani, Isnaeni; Marsuki , Nurfitriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The selection of economics education students in this research considers the suitability of the student's career interests aiming to align the graduates' learning outcomes with the study program wishes to achieve, both in the short and long term. Career interests mapping among students aims to determine the alignment of students' interests with the graduate profile achievement targets that the economics education study program wishes to achieve. This is useful as reflection material for study programs to create relevant curricula that will adequately prepare undergraduate graduates. The RMIB was used as the interest-measuring instrument in this research. Its widespread use in academic and professional contexts has demonstrated its efficacy intracking trends in students' career interests. Based on the research's findings, the three highest-ranking jobs among respondents—a total of 69 students—are the subject of career information, which is the primary concern according to the RMIB assessment. Among all students, the three most popular professional paths were computational (18%), social services (16%), and clerical (16%). The three fields with the highest career interest rates among male students were found to be clerical (20%), computational (14%), and social service (11%). In contrast, the fields with the highest career interest rates among female students were computational (20%), social service (18%), and clerical (12%). According to the research's data, there is a correlation between the learning outcomes of graduates (CPL) from the economics education study program in the teaching and educational faculty at Muhammadiyah University of Palangkaraya for the 2023–2024 academic year and the career interests of program participants.